IMAGING OF ABDOMINAL HYDATIDOSIS: A RARE PRESENTATION OF A COMMON CONDITION - Anwar, Javed; Omar, Saima; Sanaullah, Dr; Javed, Koukab (Pakistan Armed Forces Medical Journal, 2020)
A 76 year old male patient with history of progressive abdominal distension was referred for ultrasound (US) examination to look for the cause of distension. US examination followed by the CT scan abdomen and pelvis revealed multiple unilocular and multilocular cysts along with daughter cysts and cystic ascites. On the bases of imaging the case was diagnosed as abdominal hydatidosis. Imaging plays a pivotal role in the diagnosis of hydatidosis.